Applications Program Algorithms and Computer Configuration - author author (Jurnal Sistem Informasi, 2005)
Although enormous capacity of the human brain, we only use an average of two per cent of our potential brain power, we therefore have the potential to expand our brainpower and testing (testing) on a regular basis as a key method of brain power. Psychometric tests covering subjects such as personality tests which includes lateralitas tests, creativity tests which refers to the patterns of thoughts, feelings, behaviors and knowledge as well as measuring the range of human aspects. Intelligence test a test used to measure the level of one's thinking ability. One of the problems that arise in every human being has a personality that has different capabilities, including lateralitas, creativity and intelligence. In this case the characteristics that distinguish ourselves with others. Based on these issues raised and the author tries to find solutions to give a practical through the questions will be answered in psychometric tests. In the scientific writing is demonstrated several ways to solve these malasah, including using application analysis, design programs, ie algorithms programs, menu structure, program flowcharts, input and output design and configuration of the computer, and discussion about these issues.